System dynamics : an introduction for mechanical engineers - Seeler, Karl A. (Springer New York, 2014)
This essential textbook takes the student from the initial steps in modeling a dynamic system through development of the mathematical models needed for feedback control.  The generously-illustrated, student-friendly text focuses on fundamental theoretical development rather than the application of commercial software.  Practical details of machine design are included to motivate the non-mathematically inclined student. This book also: Emphasizes the linear graph method for modeling dynamic systems Offers a systematic approach for creating an engineering model, extracting information, and formulating mathematical analyses Adopts a unifying theme of power flow as the dynamic agent that eases analysis of hybrid systems, such as machinery Presents differential equations as dynamic operators and stresses input/output relationships Introduces Mathcad and programming in MATLAB Allows for use of Open Source Computational Software (R or C) Features over 1000 illustrations